The housing, feeding, training and personality of Hungarian horseback archery horses - Gál, Tímea; Tóthné Maros, Katalin (Animal welfare, Ethology and Housing Systems (AWETH), 2014)
Many researches, found in the literature prove that the proper temperament or personality in horses is one of the basic conditions of everyday efficiency. Due to this, lots of studies were made to detect the personalities of horses of different use. As far as I know no scientific survey has yet been made about horses used for horseback archery. Not only their personalities but also none of their common features (age, gender, colour, breed), neither the way they are housed or fed, nor the system of their training or their state of health has been examined yet. Our goal was to get a clearer picture of the horseback archery in Hungary, by doing a survey on all above. We collected data from 60 horses at 15 different horseback archery associations. We found out that the rate of genders is fairly equal between mares and geldings (the number of stallions is minimal) and their age is usually between 5 and 17 years. There are many different breeds among them. Horseback archery horses are usually free ranging in huge pastures, usually fed only with grass and hay, less often with simple grains like oats and barley. Their training is diverse. Ground work, cross-country riding, training under the saddle and archery training is divided equally. According to the Lloyd et al (2007) Horse Personality Questionnaire, the personality components of our archery horses are mainly different from the horses’ investigated earlier. The owners claimed that one fourth of the horses have no health problems at all. However the incidence of different wounds and injuries are relatively abundant among archery horses, which could be result of free range group keeping system.